Symphony no. 8 in F Major, op. 93 (score) - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Müller, Andreas, fl. 1815-1817 (engraver):::Contributor:::::::::::: (S: A: Steiner und Comp; Vienna, 2020)
First edition of the full score of Symphony no. 8 in F Major, op. 93. Title page engraved by Müller; music lithographed. Verso of t.p., p. [1], and last page blank. On t.p. above imprint: No. 2570. Eigenthum der Verleger. Preis [12]. Below "Wien" on t.p.: A. Müller sc. Lacks original wrapper.